Role of ultrasound-guided sacral erector spinae plane block for post-operative analgesia in pilonidal sinus surgery: A randomised trial - Mona R. Elghamry; Wail E. Messbah; Mohammad A. Abduallah; Shimaa M. Elrahwan (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Pilonidal sinus surgery (PSS) can be done with local anaesthetic infiltration, spinal anaesthesia, or general anaesthesia (GA). Erector spinae plane block (ESPB) is used for peri-operative analgesia. Erector spinae muscles extend to the sacral region, so it can provide post-operative analgesia in PSS. We evaluate the post-operative analgesic efficacy of ultrasound-guided sacral ESPB, a novel technique, in patients undergoing PSS under GA. Material and Methods: Seventy patients aged 20–60 years, ASA class I and II, and scheduled for PSS under GA were included. Patients were randomly assigned to group I (control group), who received GA only, and in group II (SESPB group), sacral ESPB was performed after induction of GA. The primary outcome was post-operative pain evaluated by visual analogue score (VAS) at arrival to the post-anaesthesia care unit (PACU), 1, 2, 4, 8, 12, and 24 hours post-operative. The secondary outcomes were time to first analgesic request post-operative, intra-operative fentanyl consumption, and complications. Results: There were significantly higher VAS scores in group I compared to group II at arrival to PACU, 1, 2, 8, and 24 hours post-operative (P = 0.017, <0.001, <0.001, <0.001, and 0.031, respectively), and no considerable changes between groups at 4 and 12 hours (P = 0.664 and 0.923, respectively). A significant decrease in intra-operative fentanyl consumption with prolonged duration to time of first analgesic request post-operative in group II compared to group I was observed (P < 0.001). No reported complications were observed. Conclusion: Sacral ESPB could provide an effective post-operative analgesia for PSS with no reported complications.